The Effect Of Market Timing On Capital Structure In Non-Financial Companies That Do IPO (Initial Public Offering) on the Indonesia Stock Exchange for the 2010-2017. - Mohammad Athian MANAN; Mahatma KUPEFAKSI; Sri HASNAWATI (Indonesia Strategic Sustainability, 2022)
Market timing theory (MTT) refers to the practice where the companies issue shares when the share prices are high prices and repurchase the shares when the share prices are low. This study aims to determine the effect of market timing on the company's capital structure and to determine whether there is a persistent (long-term) effect of market timing on the capital structure during the IPO period up to 3 years after the IPO. This study used a purposive sampling method and obtained 102 companies that conducted Initial Public Offerings on the IDX for the 2010-2017 period. The data analysis technique used is multiple linear regression analysis, while research testing is done using eviews. This study also uses four control variables, namely profitability, firm size, asset tangibility, and growth. The results of this study indicate that market timing has a significant negative effect on capital structure. However, this study also shows that market timing does not affect capital structure in the long term.